A hydrodynamic focusing microchannel based on micro-weir shear lift force - Yang, Ruey-Jen (American Institute of Physics, 2012)
A novel microflow cytometer is proposed in which the particles are focused in the horizontal and vertical directions by means of the Saffman shear lift force generated within a micro-weir microchannel. The proposed device is fabricated on stress-relieved glass substrates and is characterized both numerically and experimentally using fluorescent particles with diameters of 5 μm and 10 μm, respectively. The numerical results show that the micro-weir structures confine the particle stream to the center of the microchannel without the need for a shear flow. Moreover, the experimental results show that the particles emerging from the micro-weir microchannel pass through the detection region in a one-by-one fashion. The focusing effect of the micro-weir microchannel is quantified by computing the normalized variance of the optical detection signal intensity. It is shown that the focusing performance of the micro-weir structure is equal to 99.76% and 99.57% for the 5-μm and 10-μm beads, respectively. Overall, the results presented in this study confirm that the proposed microcytometer enables the reliable sorting and counting of particles with different diameters.